Mudanças de uso e cobertura da terra na microbacia hidrográfica do Arroio Grande, Santa Maria-RS - Zorzi, Cícero (2011)
The issues of land use changes and land covering have attracted interests, both inside and outside the scientific community, due to the accelerated process and potential environmental and socioeconomic impacts of these changes, which cause concerns at various scales from local to global. In this context, this study aims to evaluate the evolution of land use in the river basin of the Arroio Grande of Santa Maria-RS, between the years 1987 to 2009 (twenty-three years), considering six types of land use (forests, fields, agriculture, irrigated agriculture, bare soil and water depths), based on images from CBERS 2B, bands 2, 3 and 4, orbit 160, point 133, and Landsat 5 and 7 orbit 233, point 080, bands 3, 4 and 5. The Geographic Information System - SPRING 4.3.3 was used for analysis. The images of CBERS 2B and Landsat 5 and 7 provided an excellent database for the supervised classification resulting in thematic maps of Use and Land Covering of each period. The results of the different soil for each period by supervised classification varied widely showing growth deficits and for each use of one period to another, being associated with the image data used. Furthermore, this study of land use change and land covering has to contribute in assisting local managers, as mayors, local and regional government agencies, to establish policies to minimize negative impacts to the environment, for example, deforestation, and the recovery of some areas, in other words using the earth more sustainable possible through a good planning. Keywords: land use and covering, Remote Sensing, Geographic Information System, multitemporal data, Watershed.